SPECIFYING CHILD ANXIETY DISORDERS NOT OTHERWISE SPECIFIED IN THE DSM-IV - Comer, Jonathan S. (Depress Anxiety, 2012)
BACKGROUND: Anxiety disorder not otherwise specified (ADNOS) is one of the more common and impairing DSM-IV diagnoses assigned in child practice settings, but it is not clear what percentage of these assignments simply reflect poor diagnostic practices. METHODS: The present study evaluated patterns and correlates of child ADNOS in a large outpatient treatment seeking sample of anxious youth (N = 650), utilizing structured diagnostic interviewing procedures. RESULTS: Roughly, 15% of youth met diagnostic criteria for ADNOS. Overall, these youth exhibited comparable levels of clinical problems relative to youth with DSM-IV–specified anxiety disorders (AD), and roughly two-thirds of ADNOS cases exhibited symptom presentations closely resembling generalized anxiety disorder (GAD). Among ADNOS presentations resembling GAD, those failing to meet the “worries more days than not” or “worries across multiple domains” criteria showed lower internalizing symptoms than GAD youth, but comparable anxious/depressed symptoms, somatic symptoms, social problems, externalizing problems, and total problems as measured by the Child Behavior Checklist. CONCLUSIONS: Childhood ADNOS cases are prevalent and warrant clinical attention. In many cases there are only a couple, if any, clinical differences between these disorders and the ADs they closely resemble. Future work is needed to improve upon the current taxonomy of childhood ADs to specify a larger proportion of affected youth needing care.